Influence of security unrest on economic imbroglio in Nigeria: counselling intervention (2013)
This research critically looked into the security unrest as a menace of economic imbroglio in Nigeria and counselling intervention. The simple percentage was used to analyse the demographic data while t-test statistical tool was used to test the three null hypotheses that was stated at 0.05 alpha level of significance. Meanwhile the three null hypotheses stated was rejected i.e. there is no significance difference in the security unrest of Nigeria on the basis of ethnic groups was rejected, which shows that ethnic groups culminated into security unrest of the nation. Therefore recommendations were made i.e. the government must be organising conference that would involve the people from the different religions and ethnic groups on the reason why they need to tolerate themselves.